Effect of Moringa (Moringa oleifera) Leaf Flour Supplementation on Total Antioxidant Content of Sprague Dawley Rat Serum Given High-Fat Diet - Sherlin Regina Jami; Siti Fatimah-Muis; Ahmad Syauqy; Kusmiyati Tjahjono; Gemala Anjani (Jurnal Gizi Indonesia: The Indonesian Journal of Nutrition, 2022)
Background: Moringa oleifera leaf is high in quercetin which can be a source of exogenous antioxidants. Together with endogenous antioxidants, both the antioxidants will be able to counteract oxidative stress conditions.